Low-gluten shortbread enriched with sweet potato powder (Ipomoea batatas var. Portu Orange): quality and texture indicators - Bordunova, Olha; Golovko, Tetyana; Golovko, Mykola; Samokhina, Yevheniia; Vasilenko, Olha; Prymenko, Vladyslav; Bolgova, Natalia; Koshel, Olena; Oliinyk, Daria (Technology audit and production reserves, 2023)
The chemical composition of sweet potato (Ipomoea batatas var. Portu Orange), grown in Ukraine, was studied to determine its potential in shortbread technology. Portu Orange sweet potato has a high content of starch (11.2 %), natural sugars (4.7 %), dietary fiber (3.8 %) and food pigments. To obtain the highest quality characteristics and preserve the antioxidant properties of sweet potato during drying, an innovative microwave vacuum drying method was used. This allowed us to produce Portu Orange sweet potato powder with a high content of starch (43 %), natural sugars (18 %), dietary fibre (14.6 %) and preservation of food colouring properties. According to organoleptic parameters, Portu Orange sweet potato has an orange color, which was formed with a combination of anthocyanin pigmentation of the skin (orange) and β-carotene pigmentation of the flesh (light orange). In shortbread technology, Portu Orange sweet potato is used in powder form, which is an alternative to starch, sugar, orange food colorings, gluten-containing cereals and egg products. Portu Orange sweet potato powder was added to the shortbread recipe in the amount of 38 % to completely replace sugar and chicken eggs. The wheat flour in the recipe was replaced by 80 % low-gluten wheat flour and 20 % sweet potato powder. Compared to regular shortbread, the protein content increased by 24.3 % to 9.2 g/100 g, the dietary fiber content increased by 74.6 % to 10.3 g/100 g, and the ash content increased by 155.6 % to 2.3 g/100 g. The fat content of shortbread with sweet potato powder was reduced by 7.5 %, the carbohydrate content was reduced by 11.5 % and the energy value was reduced by 8 % to 407.8 kcal/100 g. Texture parameters were improved, making shortbread with sweet potato powder less hard, the hardness was reduced by 48 %, but at the same time the fracturability indicators were maintained, the fracturability was reduced by only 2 %, compared to the regular shortbread, which made it more acceptable to consumers. The obtained changes in the nutritional value of the shortbread, the improvement of the texture, the reduction of the gluten content and the presence of a high amount of biologically active substances confirm the effectiveness of using Portu Orange sweet potato powder for dietary low-gluten nutrition.